Circulating miR-141 and miR-375 are associated with treatment outcome in metastatic castration resistant prostate cancer - Zedan, A. H. (Sci Rep, 2020)
Metastatic castration resistant prostate cancer (mCRPC) is associated with high mortality, where monitoring of disease activity is still a major clinical challenge. The role of microRNAs (miRs) has been widely investigated in prostate cancer with both diagnostic and prognostic potential. The aim of this study was to investigate the relationship between circulating miRs and treatment outcome in mCRPC patients. The relative expression of five miRs (miR-93-5p, -125b-1-5p, -141-3p, -221-3p, and miR-375-3p) was investigated in plasma samples from 84 mCRPC patients; 40 patients were treated with docetaxel (DOC cohort) and 44 patients with abiraterone (ABI cohort). Blood was sampled at baseline before treatment start and at radiological progression. The plasma levels of four miRs; miR-93-5p, -141-3p, -221-3p, and miR-375-3p decreased significantly after treatment initiation in patients receiving docetaxel, and for miR-141-3p and miR-375-3p the level increased again at the time of radiological progression. In the patients treated with abiraterone, the plasma level of miR-221-3p likewise decreased significantly after the first treatment cycle. High baseline levels of both miR-141-3p and miR-375-3p were significantly associated with a shorter time to radiological progression in both cohorts. Additionally, high baseline levels of miR-141-3p and miR-221-3p were significantly associated with a shorter overall survival (OS) in the ABI cohort, while high levels of miR-141-3p and miR-375-3p were significantly associated with shorter OS in the DOC cohort. Plasma levels of miR-141-3p and miR-375-3p may predict time to progression in mCRPC patients treated with docetaxel or abiraterone. The clinical impact of these findings is dependent on validation in larger cohorts.